SUSTAINABLE NARRATIVES: REVIVING INDIAN DOLL CRAFTS IN THE AGE OF SLOW FASHION - Singh, Salam Manisana; Munjal, Kalpana (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This research investigates the revival of Indian traditional doll crafts within the global slow fashion movement context. It evaluates the potential of these crafts as sustainable economic activities, emphasizing cultural preservation, ecological responsibility, and community empowerment. Employing both qualitative and quantitative methodologies, this paper explores artisan economics, market trends, consumer preferences, and sustainable impacts. The research highlights opportunities and challenges faced by artisans, offering insights to policymakers, industry stakeholders, and academia.